Mechano-electrical feedback in the clinical setting: Current perspectives. (November 2017) - Orini, M.; Nanda, A.; Yates, M.; Di Salvo, C.; Roberts, N.; Lambiase, P.D.; Taggart, P.
Abstract: Mechano-electric feedback (MEF) is an established mechanism whereby myocardial deformation causes changes in cardiac electrophysiological parameters. Extensive animal, laboratory and theoretical investigation has demonstrated that abnormal patterns of cardiac strain can induce alteration of electrical excitation and recovery through MEF, which can potentially contribute to the establishment of dangerous arrhythmias. However, the clinical relevance of MEF in patients with heart disease remains to be established. This paper reviews up-to date experimental evidence describing the response to different types of mechanical stimuli in the intact human heart with the support of new data collected during cardiac surgery. It discusses modulatory effects of MEF that may contribute to increase the vulnerability to arrhythmia and describes MEF interaction with clinical conditions where mechanically induced changes in cardiac electrophysiology are likely to be more relevant. Finally, directions for future studies, including the need for in-vivo human data providing simultaneous assessment of the distribution of structural, functional and electrophysiological parameters at the regional level, are identified.